Unfavorable geometric imperfections in steel plate girders subjected to localized loads. (April 2021) - Kovacevic, S.; Markovic, N.; Sumarac, D.; Salatic, R.
Abstract: Recent experimental studies have shown that the current EN1993-1-5 patch loading resistance model underestimates the ultimate strength of steel plate girders in certain cases, especially for longitudinally stiffened steel plate girders and longer patch load lengths. In addition to this resistance model, the design standard allows the use of finite element analysis for the ultimate limit state. The existing design recommendations for an adequate ultimate limit state design are found insufficient. In the current paper, the imperfection sensitivity analysis of steel plate girders subjected to patch loading is performed. The paper presents a nonlinear finite element parametric study designed to determine the influence of a variety of geometric imperfections on the patch load resistance of longitudinally unstiffened and stiffened steel plate girders. Experimentally measured, buckling mode-affine, and hand-defined sinusoidal geometric imperfections were varied in the study in combination with varying patch load lengths and relative stiffnesses of the longitudinal stiffener. The ultimate strength of longitudinally unstiffened and stiffened steel plate girders increases as the patch load length is increased for all the geometric imperfections considered. For relatively small patch load lengths, the relative stiffness of the longitudinal stiffener has no significant influence on the ultimate load regardless of the geometric imperfection. For longer patch load lengths, the ultimate strength is highly dependent on geometric imperfections. The influence of the web panel aspect ratio is shown to be negligible for smaller patch load lengths regardless of the geometric imperfection, while for longer applied loads, the impact of this ratio is dependent on the geometric imperfection. Unfavorable geometric imperfections in steel plate girders subjected to patch loading are governed by the patch load length and the relative stiffness of the longitudinal stiffener. Different unfavorable geometric imperfections were found for different patch load lengths and relative stiffnesses. Local geometric imperfections defined in the upper web sub-panel yield lower ultimate strengths than global geometric imperfections (defined over the whole web depth). The lowest patch load resistances were returned for geometric imperfections that resembled the deformation at collapse (collapse-affine geometric imperfections). Although the concept of collapse-affine geometric imperfections seems impractical for design purposes (a geometrically and materially nonlinear analysis must be conducted before collapse-affine geometric imperfection shapes are determined), the use of these imperfection shapes is recommended. Highlights: Unfavorable imperfections are governed by the patch load length and the relative stiffness of the longitudinal stiffener. Collapse-affine geometric imperfections lead to the lowest patch load resistance. Local imperfections in the upper web sub-panel yield lower ultimate strengths than those defined over the whole web depth. Longitudinal stiffener has no significant impact on the ultimate load for small load lengths regardless of the imperfection. Web panel aspect ratio has a negligible effect on the ultimate load for small load lengths regardless of the imperfection.